1994
DOI: 10.1016/0741-5214(94)90277-1
|View full text |Cite|
|
Sign up to set email alerts
|

Computed tomography scanning findings associated with rapid expansion of abdominal aortic aneurysms

Abstract: An increased AAA thrombus load is associated with a higher likelihood of rapid expansion and should weigh in favor of early surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 18 publications
3
131
1
3
Order By: Relevance
“…In human AAAs, it has also been reported that a rapid lesion expansion was associated with an increased ILT load [20]. However, in very few rats, large AAAs occurred with no or a very small-sized ILT.…”
Section: Discussionmentioning
confidence: 99%
“…In human AAAs, it has also been reported that a rapid lesion expansion was associated with an increased ILT load [20]. However, in very few rats, large AAAs occurred with no or a very small-sized ILT.…”
Section: Discussionmentioning
confidence: 99%
“…Particle trajectories were governed by _ xðtÞ ¼ uðx; tÞ (1) where u was the fluid field velocity obtained from CFD. A domain of interest X was defined to encompass the entire aneurysmal region (Fig.…”
Section: Lagrangian Approachmentioning
confidence: 99%
“…It is often accompanied by the growth of ILT, and ILT formation has been linked to both the progression [1] and risk of rupture [2] of AAA. The mechanisms of ILT formation, as well as the influence of ILT on AAA biomechanics, however, are complex and poorly understood [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that the thrombus would function as a protecting factor for the aneurismatic wall against the hemodynamic stress; 10 others report the thrombus as a factor predisposing to rupture 13 and associate it with the weakening of the aneurismatic wall. [14][15] …”
Section: Introductionmentioning
confidence: 99%